A PV-Biomass off-grid hybrid renewable energy system (HRES) for rural electrification: Design, optimization and techno-economic-environmental analysis. (15th May 2022) - Kumar, Raman; Channi, Harpreet Kaur
Abstract: This research aims to bridge the gaps to produce sustainable energy cost-effectively and technically efficient. The paper explores the techno-economic-environmental viability of photovoltaic (PV)/biomass energy potential for a rural village, Sidhwanbet, Punjab, India. The data investigation was performed by HOMER Pro v3.14 software. A hybrid renewable energy system (HRES) was designed, simulated and modelled to ensure the continuous energy supply for 770 households. The proposed optimal HRES consists of a PV module, biomass generator, converter and battery with the static specification and further improved by optimization. The optimal HRES out of the best five configurations was elected with Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) based on net present cost (NPC), cost of energy generation (COE), operating cost (ƠƇ), initial capital cost (ƗƇƇ), energy generation (ĖƓ), and a renewable fraction (Ȓϯ). The selected optimal HRES has been analyzed for economic, renewable energy and environmental aspects. The sensitivity study had performed while considering the discount and inflation rate. A simulation was performed for a 10-kW biomass generator, 1.1 kW solar array, five lithium-ion batteries, and a 3.96 kW converter. Results revealed that the PV's payback period (PBP) was 1.58 years, less than the useful life of optimal HRES. The cost of constructing an HRES for 25 years was equivalent to 21087, including initial cost, operating, replacement, and project costs. Thus, 35.6% of the necessary electricity is generated with PV and 64.4% biomass under optimal conditions for a 100% renewable energy integration. The CO2 /year emission performance of optimal HRES is much better than Grid-only and PV-diesel generators. This technique may be used in rural regions in every other developing nation. Graphical abstract: Image 1 Highlights: Study of hybrid PV/Biomass/Battery energy for India rural area. Design and optimization for off-grid electricity generation system using HOMER. Technically and financially viable optimal configuration costs 0.0362 /kWh. System performance economically and environmentally analyzed by sensitivity analysis. HRES reduced GHG compared to conventional grid and PV-biogas generator only.